Cyclosporine A and FK506 as Potent Inhibitors of Streptococcus intermedius Intermedilysin-Induced NFAT-1 Activation - Heni Susilowati; Hirohiko Okamura; Katsuhiko Hirota; Kaya Yoshida; Atsushi Tabata; Hideaki Nagamune; Tatsuji Haneji; Yoichiro Miyake (Indonesian Journal of Cancer Chemoprevention, 2010)
Cyclosporine A (CsA) and tacrolimus (FK506), a member of calcineurin inhibitors, inhibit inflammation process as part of immune response. Nuclear activated T cells subfamily NFAT1 is a trascription factor responsible for the regulation of immune response genes. Streptococcus intermedius, an oral commensal bacterium, has been shown to strongly associate with liver abscess.  The S. intermedius strains produce intermedilysin (ILY), which is responsible for the bacterial virulence. Cyclosporine A and FK506 have been widely used to control NFAT activation in most of cell types, however the ability of CsA and FK506 to inhibit ILY-induced NFAT1 activation remains to be investigated. The aim of this study was to investigate the effect of CsA and FK506 on NFAT1 activation caused by ILY. Human cholangiocellular cell line HuCCT1 was stimulated with various concentrations of ILY. The cell and nuclear morphological change was observed by microscopy analysis. The NFAT1 nuclear translocation that indicates its activation was detected by immunocytochemistry. The inhibitory effect of CsA and FK506 was tested after 30 min application before ILY treatment by using immunofluorescence microscope. The results showed cell and nuclear shrinkage in ILY-treated cells. The NFAT1 was translocated to the nuclei in HuCCT1 cells, and observed in dose dependent manner.  Cyclosporine A and FK506 inhibited ILY-induced NFAT1 nuclear translocation.  In conclusion, CsA and FK506 may act as potent inflammation control agents in S. intermedius ILY-infected cells.Keywords: Cyclosporine A, FK506, NFAT1, intermedilysin